IRANIAN-AFGHAN RELATIONS ON THE THRESHOLD OF HE WITHDRAWAL OF AMERICAN TROOPS FROM AFGHANISTAN - YULDASHEVA, Guli (CENTRAL ASIA AND THE CAUCASUS, 2013)
This article analyzes the state of Iranian-Afghan relations on the threshold of the withdrawal of the main contingent of American troops from Afghanistan, planned for 2014, in the context of the current geopolitical processes in Central Asia. It examines the similarities and differences in the strivings of the various actors, the situation in Afghanistan that has arisen as a result of their clash, as well as the regional threats and challenges to Iran’s interests. The article points to the geopolitical contradictions among regional players, primarily between the U.S. and Iran, as the main variable influencing the situation in Afghanistan and its relations with Iran. According to the author, these geopolitical contradictions and the challenges and threats to regional stability ensuing from them are creating political and economic problems that are complicating the development of Iranian Afghan relations. This is making the rehabilitation of Afghanistan more difficult, including in the vitally important economic sphere, resulting in the destabilization of the situation within the country and around it.